The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1530/eje-14-0075
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in patients with idiopathic hypoparathyroidism: effect of antiepileptic drug withdrawal on recurrence of seizures and serum calcium control

Abstract: Objective: There is limited information on seizures in patients with idiopathic hypoparathyroidism (IH). We assessed seizure characteristics at presentation, subclinical seizures during follow-up, and the effect of antiepileptic drug (AED) withdrawal in IH patients. Designs and methods: Seizure characteristics were assessed in 70 patients with IH attending endocrine clinic. Provoked electroencephalography (EEG) was performed for subclinical seizures in 44 of them. AEDs were withdrawn using strict criteria, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…Treatment of these diseases must focus on calcium supplementation and not on the invalid AED therapy. Our results are consistent with the study of Modi et al [10], who indicated that patients with hypoparathyroidism could reach optimal seizure outcomes regardless of the use of AEDs. Although adult patients were included in their study, patients with seizures as the first manifestation were mainly in their childhood; this trend was similar among our included patients.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment of these diseases must focus on calcium supplementation and not on the invalid AED therapy. Our results are consistent with the study of Modi et al [10], who indicated that patients with hypoparathyroidism could reach optimal seizure outcomes regardless of the use of AEDs. Although adult patients were included in their study, patients with seizures as the first manifestation were mainly in their childhood; this trend was similar among our included patients.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study include descriptions of the prevalence of chronic complications in the Asian PHP population. Cataracts and intracranial calcification are common chronic complications of hypoparathyroidism and have been observed in 75%‐97.7% and 60%‐70%, respectively, of idiopathic hypoparathyroidism patients. These complications are related to duration of disease and Ca/P ratio .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of IH was based on hypocalcaemia, hyperphosphataemia and low intact parathyroid hormone (iPTH). 1,7,8 None of the study patients had mutation of the calcium sensing receptor (CASR) or PTH gene. However, GCM2 (R110W) mutation was present in two of them.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical and biochemical features of the cohort and their daily calcium carbonate (1-2 gm of elemental calcium) and 1,a-(OH)D (0Á5-2Á0 lg) therapy were similar to that reported earlier. 1,7,8 Details of cognitive, psychiatric and neurological assessment and abnormalities observed in 27 of 35 study subjects were reported recently. 6 The procedure adopted for assessment of other subjects was essentially the same as described earlier 6 and is briefly given in the supplement information (Please see Data S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation